PEMANFAATAN SOCIAL MEDIA ENGAGEMENT SEBAGAI INSTRUMEN PUBLIC RELATIONS DALAM REKRUTMEN MAHASISWA BARU DI ERA DIGITAL - Yeni Tri Nur Rahmawati; Nur Azizah (International Conference on Humanity Education and Society (ICHES), 2026)
This study aims to analyze the strategy of utilizing Social Media Engagement (SME) as a Public Relations (PR) tool for new student recruitment amidst the increasingly competitive environment of higher education institutions in 2026. In today's digital era, two-way interaction through social media platforms is no longer merely an information channel, but a strategic tool for building trust and institutional image. The research method used was descriptive qualitative, conducted through observations on TikTok, Instagram, and LinkedIn, as well as in-depth interviews with university public relations teams. The results showed that high levels of engagement, such as comments, content sharing, and direct messages, positively correlated with prospective student interest in registering. A personalized, transparent, and responsive content strategy is key to PR's success in converting followers into applicants. This study concludes that transforming the role of PR from merely distributing press releases to managing digital communities is crucial for effective recruitment in the future.